Oxford handbook of palliative care - Watson, Max S.; Lucas, Caroline; Hoy, Andrew; Wells, Jo (Oxford University Press, 2009)
Revised throughout with an additional emphasis on nursing care, this handbook is a concise and authoritative guide to modern palliative care. An ideal resource for the busy professional management of patients with end of life care needs.